Augmenting the VLE using widget technologies. (16th March 2011) - Wilson, Scott; Sharples, Paul; Griffiths, Dai; Popat, Kris
Can widget technologies revolutionise the virtual learning environment (VLE) and challenge the dominant design of e-learning? Are widgets ready to be deployed in today's VLEs? The authors describe an experimental implementation of the Moodle VLE using the W3C widget specification and Google Wave Gadget API to replace existing core features. This raises four challenges: 1) by replacing most of the functionality of the VLE with simple reusable applications, the core functionality and design of the VLE is challenged; 2) by allowing these applications to be extracted and used in personal learning environments (PLEs), the hegemony of the institutional system is challenged; 3) by conducting learning activities in small discrete applications, the model of student tracking is challenged; 4) synchronous, live updating applications challenges the model of user behaviour for the VLE. The paper also describes further work in adding widget technology to other VLEs using the IMS Basic learning tools interoperability (LTI) specification.